Emo : how fans defined a subculture - Fathallah, Judith (Fandom & culture., 2020)
"This book explores how online fandom has shaped the definition of emo, with significant implications both for millennial constructs of gender and contemporary fan studies. 'Emo,' an abbreviation of emotional hardcore, refers to both a music genre and a youth scene notable for its androgynous style. Through study of online fandom's interaction with the music industry, I will demonstrate fandom's key role in defining 'emo' as a concept and genre after 2001, especially its implications for gender constructions through popular music"--